Scholars as Audiences, Symbolic Boundaries, and Culturally Legitimated Prime-Time Cable Drama - Wayne, Michael (Global Media Journal - German Edition, 2015)
This article addresses Jason Mittell's controversial essay “On Disliking Mad Men” (2010) in the cultural context of post-network television. The author uses 72 critical reviews of five HBO series to place Mittell's argument alongside other rhetorical strategies that resist the prestige associated with high-status prime-time cable dramas. In relation to these rhetorical strategies, the troubled publication history of and negative scholarly reactions to Mittell's essay are understood as indicative of elite post-network television audiences policing the symbolic boundaries surrounding culturally legitimated texts.